Islamic conceptualisation of knowledge management - Hj. Yaakub, Muhamadul Bakir (Science Publication, 2011)
This study is an attempt to address “The Fundamental Theory of Knowledge Management” from Islamic point of views, to draw the notion of “Islamic Worldview” of knowledge, especially in terms of understanding its nature in the reality of knowledge society as a step toward conceptualizing “Islamic Knowledge Management” (IKM) as an answer to the uncertainty situation of contemporary knowledge development, management and utilization especially for Muslim user and application. To obtain this, they have to explore new techniques and processing tools that helps them harness knowledge in according to their conceptual believe system, especially in term of knowledge investigation and sharing in which help them to improve their vicegerent (VG) status and humanistic relationship. Approach: Indeed, knowledge should be realised comprehensively. Thus, with the assumption that once knowledge is realized and managed, then it is possible to look at its behaviors, functions and process of development in the form of scientific realm. Hypothetically, if there were no single theory formulated to identify the nature of knowledge, then how it can be managed and achieved its goals. Results: In this regard, IKM as an Islamic system is intended for particular areas of application and objectives based on “knowledge intensive processing action” (KIPA), in which it is depending on some human expert intervention in order to establish a comprehensive and integrated organizational culture, commitments and management, or to better perform the process in producing a production, marketing campaigns, systems analysis and design and strategy in reducing operational cost and business risk, in improving decision making for strategic future development and identifying new technical approaches in problem solving, or even for the purpose to harmonize inter-cultural and personalities gaps within an organizational community. Conclusion: Obviously, knowledge classification is very much influenced by the way a society conceptualizes and realizes knowledge. Any classification will lead to a way of utilization. Therefore, any success achieved by a person was absolutely an output of his knowledge understanding and knowledge growth within himself. In this status, as a human, he might be influenced by a certain situation, limitation and constrain internally or externally that lead him to persuade either body knowledge or the functional usage of knowledge in making his own individual success i.e. user-centric based values.